Vertical and horizontal asymmetries are related to slower sprinting and jump performance in elite youth female soccer players - Bishop, C.; Read, P.; McCubbine, J.; Turner, A. (The Journal of Strength and Conditioning Research, 2021)
Interlimb asymmetries have been shown to be greater during vertical jumping compared with horizontal jumping. Notable interlimb differences have also been established at an early age in male youth soccer players. Furthermore, given the multiplanar nature of soccer, establishing between-limb differences from multiple jump tests is warranted. At present, a paucity of data exists regarding asymmetries in youth female soccer players and their effects on physical performance. The aims of this study were to quantify interlimb asymmetries from unilateral jump tests and examine their effects on speed and jump performance. Nineteen elite youth female soccer players performed a single-leg countermovement jump (SLCMJ), single, triple, and crossover hops for distance, and a 20-m sprint test. Test reliability was good to excellent (intraclass correlation coefficient = 0.81-0.99) and variability acceptable (coefficient of variation = 1.74-5.42%). A 1-way analysis of variance highlighted larger asymmetries from the SLCMJ compared with all other jump tests (p < 0.05). Pearson's correlations portrayed significant relationships between vertical asymmetries from the SLCMJ and slower sprint times (r = 0.49-0.59). Significant negative relationships were also found between horizontal asymmetries during the triple hop test and horizontal jump performance (r = -0.47 to -0.58) and vertical asymmetries during the SLCMJ and vertical jump performance (r = -0.47 to -0.53). The results from this study highlight that the SLCMJ seems to be the most appropriate jump test for identifying between-limb differences with values ~12% showing negative associations with sprint times. Furthermore, larger asymmetries are associated with reduced jump performance and would appear to be direction specific. Practitioners can use this information as normative data to be mindful of when quantifying interlimb asymmetries and assessing their potential impact on physical performance in youth female soccer players.